PENGARUH HUMAN CAPITAL TERHADAP ECONOMIC VALUE ADDED PADA SEKTOR UMKM DI PROVINSI BALI - Komang Agus Rudi Indra Laksmana; I Ketut Merta (Master of Management, Mataram University, 2020)
Micro, Small and Medium Enterprises (MSMEs) have a role in accelerating the economy of the community. The quality of MSMEs is largely determined by competitive advantage by utilizing resources that focus on developing or obtaining valuable resources and capabilities. The UMKM sector with intangible assets of MSME players, namely human capital towards the creation of economic value added or Economic Value Added (EVA) in MSMEs. The purpose of this study was to examine and explain the effect of human capital of MSME players in Bali on the achievement of Economic Value Added (EVA). This study uses a positivism approach. The population in this study was the UMKM in Bali Province, amounting to 450 UMKM, with a research sample of 212 MSMEs in Bali Province. The results of research findings that human capital have a significant positive effect on the creation of economic value added (EVA) in MSMEs. The average level of EVA on MSMEs is negative, which means that in general, MSMEs in Bali province have not been able to achieve EVA in their business management.The limitation in this study is the incomplete availability of MSME financial reports. In addition, further research is expected to add other contingencies, such as personality and defense mechanisms.